2021
DOI: 10.1021/acs.biomac.1c00228
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Gold Nanoparticle-Conjugated Cellulose Nanoonions Alleviate Aβ42 Fibrillation-Induced Toxicity via Regulation of Oxidative Stress and Ion Homeostasis

Abstract: Inhibition of hen egg white lysozyme (HEWL) and Aβ42 fibrillation have been established as the main models for the treatment of systemic lysozyme amyloidosis and Alzheimer’s disease (AD), respectively. Several antiamyloidogenic nanomaterials have been developed over the period; however, their intracellular mechanism of action is still not well understood. In this context, plant-based, gold-conjugated, injectable, hydrophilic cellulose nanoonions (CNOs), viz., DH–CNO (∼60 ± 5 nm) and LC–CNO (∼55 ± 12 nm), were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…This could also be due to changes in oxygen levels leading to oxidative stress which can influence mitochondrial function. There are very few studies that have examined the effect of nanocellulose on oxidative stress, but some in vivo research has suggested that various forms of nanocellulose and cellulose nanocrystal-derived nano-onions can induce a slight increase in reactive oxygen species (ROS) generation in gut epithelium ( DeLoid et al, 2019 ), and modulate oxidative stress in HEK293 cells ( Abidi et al, 2021 ). Cationic derivatives of crystalline crystalline nanocellulose have induced mitochondrial ROS and ATP release in a mouse macrophage cell line (J774A1) and peripheral blood mononuclear cells ( Sunasee et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This could also be due to changes in oxygen levels leading to oxidative stress which can influence mitochondrial function. There are very few studies that have examined the effect of nanocellulose on oxidative stress, but some in vivo research has suggested that various forms of nanocellulose and cellulose nanocrystal-derived nano-onions can induce a slight increase in reactive oxygen species (ROS) generation in gut epithelium ( DeLoid et al, 2019 ), and modulate oxidative stress in HEK293 cells ( Abidi et al, 2021 ). Cationic derivatives of crystalline crystalline nanocellulose have induced mitochondrial ROS and ATP release in a mouse macrophage cell line (J774A1) and peripheral blood mononuclear cells ( Sunasee et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…For precise characterization of the attachment of TNF-α and IL-6 on the AuNPs, MALDI-TOF MS studies were carried as per our previous report. , The detailed procedure for this is already described in Section S2 in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The DCFDA assay was performed as per our previous reports with slight modification. 22,27 The detailed procedure is given in the Supporting Information (Section S7).…”
Section: Stability Of Rbc Ghosts Under Different Ph and Nacl Ion Conc...mentioning
confidence: 99%
“…32,33 For evaluating the oxidative stress levels of cells due to bare and proteincloaked NPs, intracellular reactive oxygen species (ROS) estimation was performed as described earlier. 32,33 Further, for the direct visualization of the ROS generation, fluorescence microscopic analysis was performed for bare and protein-cloaked FITC-conjugated NPtreated cells. For assessing the internalization of bare and proteincloaked NPs inside the cells under in vitro conditions, cellular internalization studies were carried out on cell lines, viz., HEK-293 and human adenocarcinomic alveolar basal epithelial cells (A549).…”
Section: Methodsmentioning
confidence: 99%
“…For cell viability studies of the bare and protein-cloaked NPs, the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was carried out using human embryonic kidney (HEK-293) cells following our previous protocol with minor modifications. , For evaluating the oxidative stress levels of cells due to bare and protein-cloaked NPs, intracellular reactive oxygen species (ROS) estimation was performed as described earlier. , Further, for the direct visualization of the ROS generation, fluorescence microscopic analysis was performed for bare and protein-cloaked FITC-conjugated NP-treated cells. For assessing the internalization of bare and protein-cloaked NPs inside the cells under in vitro conditions, cellular internalization studies were carried out on cell lines, viz.…”
Section: Methodsmentioning
confidence: 99%